Self-assembled CeO2 on carbon nanotubes supported Au nanoclusters as superior electrocatalysts for glycerol oxidation reaction of fuel cells - Yuan, W.; Zhang, J.; Shen, P.; Li, C.; Jiang, San Ping (2016)
© 2015 Elsevier Ltd. All rights reserved. One of the critical challenges in energy conversion using fuel cells is the development of non-Pt based electrocatalysts with high activity and stability. Herein, CeO2 nanoclusters of 1.5 nm supported on 1-pyrenecarboxylic acid (PC) functionalized multi-walled carbon nanotubes (PC-MWNTs) were synthesized via sequential polyelectrolyte functionalization and microwave-assisted self-assembly, and subsequently used as a support of gold (Au) NPs for glycerol oxidation reaction. The hybrid Au/CeO2/PC-MWNT electrocatalyst shows excellent activity and durability, achieving a peak current density 28 times that of the commercial Pt/C catalyst; at a practical fuel cell operation potential of -0.3 V vs. SCE, it exhibits a current density 1.6 times that of Pt/C. In addition, after polarization at -0.3 V vs. SCE for 1800s, the current density is 2.5 times that of Pt/C. This is probably the first report of a higher catalytic performance of Au-based catalysts than that of the commercial Pt/C catalysts at practical fuel cell operation potentials. The work not only provides an economical and facile strategy to synthesize oxide-based nanoclusters (NP size < 2 nm) as a support of Au-based electrocatalysis, but also offers a superior electrocatalyst to replace Pt-based ones for glycerol oxidation reaction in glycerol fuel-based direct alcohol fuel cells.